Eksistensi Hukum Pidana Adat (Delik Adat) dalam KUHP Nasional Baru - Hasim Aji Muzadi; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The recognition of customary criminal law in the new National Criminal Code (KUHP) represents a significant breakthrough in Indonesia's criminal law reform. This research examines the existence of customary criminal law within the National Criminal Code, focusing on normative regulation, implementation challenges, and prospects for actualization using a descriptive-analytical normative juridical approach. The findings reveal that recognition is normatively regulated through Article 2 paragraph (1), Article 597, and Article 66 paragraph (1) letter f of the National Criminal Code, yet this recognition requires the existence of Regional Regulations formulating still-existing customary norms. Its implementation faces three main challenges: normative conflict with the formal legality principle threatening legal certainty, the absence of clear implementing regulations, and the diversity of customary law that is difficult to standardize. On the other hand, this recognition opens opportunities for strengthening restorative justice and national legal identity rooted in Pancasila and national culture. This research recommends accelerating the formulation of Regional Regulations, issuing technical guidelines for identifying and codifying customary law, enhancing law enforcement capacity, and strengthening cross-sectoral coordination.